Behavior of High Strength Concrete Columns Intersected by Normal Strength Concrete Beams - Omar Faisal Hamad; Ahmed Heidayet Mohammad (Zanco Journal of Pure and Applied Sciences, 2023)
Under axial compression stress, ten column specimens were investigated, one of which was an isolated column specimen, while the others were beam-column specimens with varying concrete strengths intersected with normal strength concrete. The column axial strength and behaviour were studied with the following parameters: different ratios of column concrete strength to beam concrete strength ( / ) (1, 1.58 and 1.89), different confinement ratios (ties) at the column location that intersected with the beam (0, 0.0049, and 0.0098), and the effects of confining beam-column joint by beams on two sides of the column. The experimental results demonstrated that the strength of the inner beam-column joint depends on the confining of the beam-column joint by ties. The ties change the failure location from the beam-column joint to the upper and lower column. The existence of ties overcomes the problem of normal concrete strength between high strength concrete (HSC). The proposed method is compared with ACI and CSA equations to show the efficiency of the models. ACI model gave significantly underestimated results.